Seismic Response of Plan-Asymmetric Structures with Diaphragm Flexibility - Hamed Eivani; Abdolreza S. Moghadam; Armin Aziminejad; Masoud Nekooei (Shock and Vibration)
The seismic behavior of asymmetric structures with a flexible diaphragm was studied by conducting inelastic dynamic time-history analyses. Asymmetric structures with different configurations of mass, stiffness, and strength centers, in combination with a wide range of diaphragm flexibility, were evaluated. The behavior of structures was studied by considering three aspects: (1) effect of structural asymmetry on diaphragms deformation; (2) effect of diaphragm flexibility on demands of the lateral load-resisting elements; (3) optimum configuration of mass, stiffness, and strength centers to limit important engineering demand parameters in asymmetric structures with a flexible diaphragm. The results showed that the shear-dominant deformation of diaphragms is sensitive to both structure asymmetry specifications and the degree of diaphragm flexibility; therefore, it can be used for the qualitative classification of the seismic behavior of structures. Also, the center of strength in structures with flexible diaphragm is more important relative to the stiffness center and has a significant effect on engineering demands at all levels of diaphragm flexibility. Moreover, it was found that a suitable configuration of centers in torsionally stiff structures depends on the degree of diaphragm flexibility, in addition to the intensity of earthquakes (structure yield level) and selected engineering demand parameter.